Mast Cells in Stress, Pain, Blood-Brain Barrier, Neuroinflammation and Alzheimer’s Disease - Kempuraj, Duraisamy; Mentor, Shireen; Thangavel, Ramasamy; Ahmed, Mohammad E.; Selvakumar, Govindhasamy Pushpavathi; Raikwar, Sudhanshu P.; Dubova, Iuliia; Zaheer, Smita; Iyer, Shankar S.; Zaheer, Asgar (Frontiers in Cellular Neuroscience, 2019)
Mast cell activation plays an important role in stress-mediated disease pathogenesis. Chronic stress cause or exacerbate aging and age-dependent neurodegenerative diseases. The severity of inflammatory diseases is worsened by the stress. Mast cell activation-dependent inflammatory mediators augment stress associated pain and neuroinflammation. Stress is the second most common trigger of headache due to mast cell activation. Alzheimer’s disease (AD) is a progressive irreversible neurodegenerative disease that affects more women than men and woman’s increased susceptibility to chronic stress could increase the risk for AD. Modern life-related stress, social stress, isolation stress, restraint stress, early life stress are associated with an increased level of neurotoxic beta amyloid (Aβ) peptide. Stress increases cognitive dysfunction, generates amyloid precursor protein (APP), hyperphosphorylated tau, neurofibrillary tangles (NFTs), and amyloid plaques (APs) in the brain. Stress-induced Aβ persists for years and generates APs even after several years stress of exposure. Stress activates hypothalamic-pituitary adrenal (HPA) axis and releases corticotropin-releasing hormone (CRH) from hypothalamus and in peripheral system, which increases the formation of Aβ, tau hyperphosphorylation, and blood-brain barrier (BBB) disruption in the brain. Mast cells are implicated in nociception and pain. Mast cells are the source and target of CRH and other neuropeptides that mediate neuroinflammation. Microglia express receptor for CRH that mediate neurodegeneration in AD. However, the exact mechanisms of how stress-mediated mast cell activation contribute to the pathogenesis of AD remains elusive. This mini-review highlights the possible role of stress and mast cell activation in neuroinflammation, BBB and tight junction disruption and AD pathogenesis.